In Situ Synthesis and Immobilization of Nanosilver on Knitted Cellulose Fabric - Zulfiqar Ali Raza (Journal of Natural Fibers, 2018)
Herein, we report simple clean route for producing antibacterial knitted cellulose fabric. Silver nanoparticles (SNPs) were successfully synthesized and impregnated on the fabric by using starch as reducing and stabilizing agents under standard autoclave setup. The results expressed successful synthesis of SNPs with a mean diameter 25.72 ± 3.53 and corresponding zeta potential of −41 mV. The scanning electron microscopy analysis indicated that the surface of fabric was embedded with SNPs. The energy dispersive X-ray of SNPs-coated cotton fabric proved the incidence of SNPs. The SNPs impregnated knitted cellulose fabric expressed good broad spectrum antibacterial activity.